Temporal context-guided memory capabilities in rodents - Benjamin J. A. Slater; Christopher I. Petkov; Alexander Easton (Scientific Reports)
Abstract Environmental contexts serve as powerful cues for episodic memory, allowing humans to recall events tied to specific settings. While rats can learn context-specific associations and temporal order, their ability to manage multiple contexts and rapidly adapt to changes in context remains unclear. This study investigated whether rats could order objects across two distinct contexts. Eight Lister Hooded rats were trained in a dual-context maze, where each context contained a pair of objects. In each trial, rats entered the maze, selected an object, and then re-entered either the same or a different context to complete the trial in the correct temporal order. Six rats successfully learned object order within a single context, but only two reached criterion in the more complex two-context condition. Group error analyses revealed a partial reliance on a procedural learning strategy and a tendency to favour one context, where prior location influenced object selection in subsequent trials. While two rats successfully adapted to the two-context condition beyond these simple strategies, most struggled with context switching, exhibiting perseveration difficulties—a trait also observed in some humans. These findings highlight the evolutionary foundations of context-guided memory and reveal remarkable individual variability in the ability to flexibly navigate multiple contexts.